Temperature Effect on the Thermal Conductivity of Expanded Polystyrene Foamed Concrete: Experimental Investigation and Model Correction - Jinyan Shi; Yuanchun Liu; Baoju Liu; Dan Han (Advances in Materials Science and Engineering)
In this research, ultralightweight expanded polystyrene foamed concrete (EFC) was made by the chemical foaming method, and its thermal insulation property was measured by the transient method at different environment temperatures (from −10 to 40°C). Then, the effect of temperature and EPS volume fraction on the thermal conductivity and dry density of EFC were observed. Ultimately, the Cheng–Vachon equation was modified by introducing the temperature parameter. The results indicated that EFC thermal conductivity decreases with increasing temperature. It was also demonstrated that the suitable volume of EPS particles can not only decrease the EFC thermal conductivity but also reduce the impact of temperature on the thermal conductivity. The thermal conductivity of EFC at different temperatures was accurately predicted in this study using the proposed model.